Using geographic informations systems for solid waste management - Platonov A.A.; Markov D.O. (Научно-технический вестник Брянского государственного университета)
In this article the problem of placement of solid waste landfills is analyzes. We have analyzed the characteristics of the subject area and revealed the necessity of using modern geographic information systems to solve this problem. On the basis of the research we offer solutions to the problem.